Perceived Stigma in People Affected by Leprosy in Leprosy Village of Sinatala, Tangerang District, Banten Province, Indonesia - Astutik, Erni; Gayatri, Dwi (UI Scholars Hub, 2018)
Leprosy is a disease of neglected tropical diseases (NTDs) which becomes a global problem and causes the perceived stigma in people affected by leprosy. This study aimed to determine most dominant factors affecting perceived stigma in people affected by leprosy in leprosy village of Sitanala, Tangerang District, Banten Province, Indonesia. The data used was secondary data taken from cross-sectional survey of a thesis which determined factors related to perceived stigma of leprosy in leprosy village of Sitanala, Tangerang, Indonesia. Samples were selected by purposive sampling. The results of the study showed that factors related to perceived stigma were level of education, perception of knowledge about leprosy, level of disability, and cultural values. There was modification effect between the level of disability and perception of knowledge about leprosy, OR1=4.82 (95% CI 1.26-18,34) and OR2=1.18 (95% CI 0.2-6.98). The dominant factor is level of education with PAR% = 38.8%.